Poly (1-Aminonaphthalene) As A Chemosensor For Selective Detection Of Iron(III) ION - Nizar, Syaza Atikah (2020)
This study describes the synthesis of poly (1-aminonaphthalene) and its application as a chemosensor for the detection of Fe3+ by colorimetric and fluorimetric method. The conjugated polymer was synthesized via chemical oxidative polymerization method using FeCl3 as a catalyst. The obtained polymer was characterized by different spectroscopic methods including Fourier Transform Infrared (FT-IR), Proton Nuclear Magnetic Resonance (1H-NMR) and Gel Permeation Chromatography (GPC).